The Role of Urban Density in Achieving Sustainable Cities: Amsterdam as a Case Study - Radi, Sama; Al-Rikabi, Nada (Al-Adab Journal, 2025)
There is a general consensus that compact urban forms represent a more sustainable future over the past thirty years. However, recent research has revealed complex issues surrounding the urban environment, which may lead to urban intensification policies that do not align with the goals of creating more sustainable cities. Rather than relying on a single solution, there is a need to understand that the urban future will be diverse, and urban intensification should be viewed as a means to achieve sustainable urban form.Furthermore, policies of intensification are likely to succeed when they adapt to the current urban landscape of the targeted neighborhoods. However, recent literature does not suggest a return to urban sprawl. By focusing on smaller scales, urban design can address criticisms regarding the viability of the compact city, while highlighting the cultural, political, social, and institutional changes needed to move away from random sprawl, which has become an integral part of urban development over the past fifty years.This research explores the impact of urban intensification on achieving sustainability goals in cities, as intensification is considered an effective strategy for improving the efficiency of environmental resource use and enhancing quality of life. The research emphasizes the importance of intensification as a necessary tool for achieving urban sustainability, stressing the need for a balanced approach that combines environmental, social, and economic benefits to ensure a sustainable urban future.The theoretical framework has been applied to a high-density city model, specifically Amsterdam, to highlight how these goals can be achieved in a practical context. The research includes an analysis of the intensification policies and practices implemented in Amsterdam.